A Review on "The Prospective Assessment and Evaluation of Prescriptions during Pregnancy” - Sharma, Shyam; Sharma, Yogesh (Journal of Drug Delivery and Therapeutics, 2019)
More than 80% of pregnant women take OTC or prescription drugs during pregnancy, with only 60% of these patients consulting a health care professional when selecting a product. Common pregnancy-associated conditions include cough, cold, allergies, gastrointestinal disorders, and pain. The cough, cold, and allergy products most widely used during pregnancy are antihistamines, decongestants, antitussives, and expectorants. Current updates to the immunization schedule include administering tetanus, diphtheria, and acellular pertussis (Tdap) vaccine with each pregnancy. Influenza vaccination should also be recommended for all pregnant women and can be given in any trimester. Keywords: Prescriptions in Pregnancy, Vaccination, OTC drugs.